The therapeutic potentials of apelin in obesity-associated diseases. (1st June 2021) - Castan-Laurell, I.; Dray, C.; Valet, P.
Abstract: Apelin, a peptide with several active isoforms ranging from 36 to 12 amino acids and its receptor APJ, a G-protein-coupled receptor, are widely distributed. However, apelin has emerged as an adipokine more than fifteen years ago, integrating the field of inter-organs interactions. The apelin/APJ system plays important roles in several physiological functions both in rodent and humans such as fluid homeostasis, cardiovascular physiology, angiogenesis, energy metabolism. Thus the apelin/APJ system has generated great interest as a potential therapeutic target in different pathologies. The present review will consider the effects of apelin in metabolic diseases such as obesity and diabetes with a focus on diabetic cardiomyopathy among the complications associated with diabetes and APJ agonists or antagonists of interest in these diseases.